"I Know Which Devil I Write for": Two Types of Autonomy Among Czech Journalists Remaining in and Leaving the Prime Minister's Newspapers. (January 2023) - Kotisova, Johana; Císařová, Lenka W.
This paper examines two different understandings of professional autonomy among journalists currently and formerly working at Mafra, a Czech media house acquired in 2013 by Andrej Babiš, who in 2017 became the Czech Prime Minister. We build on existing research of local trends in media ownership and journalistic autonomy to ask the following questions: What differentiated the experience of journalists who exited the organization after the ownership change from that of those who stayed put? How did the two groups understand professional journalistic autonomy? Based on the thematic analysis of twenty semistructured interviews with ten journalists who stayed in the media house after Babiš's acquisition and ten journalists who left, we argue that in the journalists' narratives, the two decisions reflect two different notions of autonomy: autonomy-as-a-practice and autonomy-as-a-value. While our findings add to the scarce empirical research on journalists' lived experiences of the region's mediascape marked by growing comingling and concentration of political, economic and media power, we also suggest that the autonomy-as-a-practice and journalists' agency should be further studied as a possible way how to perform and promote journalistic autonomy even in illiberalizing contexts—in Central and Eastern Europe and beyond.